Justification of urolithiasis prevention and metaphylaxis improvement on the basis of socio-economic characteristics of patients. - Detsyk, О. Z.; Solomchak, D. B. (Medicni Perspektivi, 2016)
In order to determine the directions of urolithiasis prevention and metaphylaxis improvement there was conducted a retrospective epidemiological study of a representative sample of 443 patients (study group, 403 – without and 40 – with recurrences) and 203 patients with other, mainly acute urological pathology (control group). It was established that urolithiasis affects mainly people of the working age (75%). Prevalence of pathology increases with age (OR=3.93; 95% CI=1.64-9.44), as well as recurrences formation (2.44; 1.21-4.93) occurring in 10-20% of patients with urolithiasis older than 40 years. It was proved that social and economic burden of the disease increases with recurrent stone formation due to the increase of low well-being (3.43; 1.77-6.65), unemployment (2.26; 1.14-4.45) and disability (3.93; 1.64-9.44). Conclusion is drawn on the need of improving prevention, first of allmetaphylaxis, technologies, by sharing of responsibilities between urologists and family doctors.